Progressive Multifocal Leukoencephalopathy: Cavitary White Matter Lesions - Alquist, Caroline Raasch (2012)
Progressive Multifocal Leukoencephalopathy (PML) is a fatal demyelinating disorder of the central nervous system caused by the opportunistic neurotropic Polyomavirus JCV. PML typically presents in immunocom-promised individuals; is considered an AIDS defining condition; and is clinically characterized by cognitive defects, coordination problems, limb paresis, and speech disturbances. MRI can identify the characteristic bilaterally asymmetrical lesions that favor the subcortical frontal and parietal lobes as hypo-intensities on T1-weighted images and as hyper-intensities on T2-weighted images. Grossly, these areas appear discolored by a dusky, yellow-brown hue with the rare appearance of cavitation. No known therapeutic agent can specifically halt the progression of PML, and survival time after diagnosis averages less than two years. In this submission, we present a photo depicting striking lesions of severe PML of the cavitary type.